The impact of algorithmic training in basic taekwondo strikes on the technical preparedness of young athletes - Semenova, G.I.; Erkomayshvili, I.V.; Ryabov, G.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to develop and implement a training algorithm that helps improve the technique of basic strikes in WTF taekwondo practitioners. Methods and structure of the study. The main method of research in the pedagogical experiment was testing basic striking techniques. 20 taekwondo practitioners aged 12-14 from Yekaterinburg took part in the experiment. An algorithmic approach was developed, according to which the experimental group trained for three months. This method involved step-by-step training, with each step representing a specific set of actions aimed at forming and improving motor skills. The entire algorithm was divided into phases (preparatory, initial learning, consolidation and improvement). The phases were divided into steps (more detailed learning, in which, if an error occurs in the execution of an element in a strike, it is necessary to return to the previous step). Results and conclusions. As a result of the study, the experimental group improved their technique in the following basic strikes: front kick with the leading leg (ap chagi), side kick with the rear leg (dole chagi), and 180° turn kick (tit hurio chagi). Thus, the effectiveness of algorithmisation as a means of optimising the teaching of basic taekwondo kicks has been experimentally proven.